PENGARUH GREEN PRODUCT KNOWLEDGE DAN GREEN PERCEIVED RISK TERHADAP GREEN PURCHASE INTENTION YANG DIMEDIASI OLEH GREEN TRUST (STUDI KOMPARASI ANTARA PRODUK AIR MINERAL AQUA DENGAN LE MINERALE) - Putri, Saidina; Fadhila Rahma, Tri Inda; Aisyah, Siti (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: This study aims to analyze the influence of green product knowledge and green perceived risk on green purchase intention mediated by green trust, with a comparative study between Aqua and Le Minerale mineral water products. The data analysis technique used the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through the SmartPLS 3.0 application. The results showed that green product knowledge has a significant positive effect on green purchase intention, both directly and through the mediation of green trust, on both products. Green perceived risk also has a positive effect on green purchase intention, but with different levels of significance between Aqua and Le Minerale. In Aqua, the influence of green perceived risk on green purchase intention is greater than in Le Minerale. The results of the comparative analysis showed that the level of green product knowledge and green trust was higher in Aqua than in Le Minerale, while green perceived risk was higher in Le Minerale than in Aqua. The results of the hypothesis test using a paired sample T-Test confirmed a significant difference between the two brands in terms of the variables tested.Keywords: Green Product Knowledge, Green Perceived Risk, Green Trust, Green Purchase Intention